Optimized Vector Control Using Swarm Bipolar Algorithm for Five-Level PWM Inverter-Fed Three-Phase Induction Motor - Yaseen, Farazdaq R.; Al-Khazraji, Huthaifa (International Journal of Robotics and Control Systems, 2025)
Induction motors (IMs) are commonly used in various applications such as robotics and automotive industries. This paper proposes an optimization of two proportional-integral (PI) controllers for a multi-level pulse width modulation (PWM) voltage-fed inverter linked to a three-phase IM. The paper aims to enhance inverter output quality, minimize harmonic distortion, and ensure robust, stable performance. The swarm bipolar algorithm (SBA) is introduced to elaborate the searching of the best settings of the PI controllers to achieve the desired response. Â Harmonics lead to increased system losses by creating negative torque components. To address this problem, two modulation algorithms are proposed to generate three-phase voltage with minimum harmonics including space vector PWM (SVPWM) inverter and sinusoidal PWM (SPWM). Simulation results based on MATLAB/Simulink environment for various operation conditions such as sudden loads change and speed changes reveal that the proposed controller enhances the system's performance. Moreover, the five-level SVPWM inverter has a minimum threshold harmonic distortion (THD) compared to the five-level SPWM inverter where the THD is decreased from 40.24% for SPWM method to 13.67% for the SVPWM method.